Comparación del efecto de castración química mediante jugo de limón vs cloruro de sodio sobre el comportamiento productivo en Cobayos - Calderón Chamorro, Yessenia Fernanda (2022)
At the Latin American level, the inter-Andean region has been characterized by the production and consumption of guinea pig meat (Cavia porcellus), a traditional food that is perpetuated and over time, currently, guinea pig farms through the establishment of production systems intensive supply the demand of potential clients specialized in the preparation of traditional food, very sustained in dishes with guinea pigs in different presentations. Proper management of guinea pig production becomes an essential need to obtain high-quality meat with optimal performance in the carcass\; purposes that are achieved through gonadectomy or castration, since it accelerates the growth process, limits aggressive behavior and prevents scarring of the skin, as well as low feed conversion. The application of sclerotic substances in chemical castration is beneficial, for which the guinea pigs do not present stress or pain. The general objective of this study was to evaluate the effect of chemical castration in guinea pigs in the growth stage by comparing 4% sodium chloride and citric acid. The experimental work was developed in the province of Carchi, Montúfar canton, San Gabriel city, San José neighborhood. In the present investigation, the DCA statistical design was adopted, to apply two different sclerotic substances (T2 and T3 and a control T1), for this purpose guinea pigs of the Peru breed were selected through good animal welfare criteria, identified, registered and distributed in different groups. The performance data shows the usefulness of this study, presenting results on feeding, weight gain and behavior analysis through the Adeva analysis and Tukey test, therefore, the results show that the castration option used through the application of sclerotic substances is very effective to carry out a high yield to the carcass.